2021
DOI: 10.1136/bmjopen-2021-048975
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab in the treatment of adult gliomas: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the efficacy and safety of bevacizumab (BEV) in patients with glioma.DesignSystematic review and meta-analysis.ParticipantsAdults aged 18 years and above, whose histology was confirmed to be malignant glioma.Primary and secondary outcome measuresThe main indicators included progression-free survival (PFS) rate and overall survival (OS) rate, and the secondary indicators were adverse reactions.ResultsA total of 11 clinical centre trials were included in this study for meta-analysis, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…46 The evidence suggests that bevacizumab can prolong the progression-free survival (PFS) of patients with glioma within 18 months but can't prolong the OS. 47 Cetuximab and nimotuzumab target epidermal growth factor receptor (EGFR), which can block its ligand activity, induce apoptosis, antiangiogenesis, and thus achieve the effect of inhibiting GBM cells. 48 In a phase II clinical study of cetuximab treated in patients with relapsed GBM, cetuximab did not benefit patients from PFS and OS, regardless of whether accompanied by EGFR amplification.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…46 The evidence suggests that bevacizumab can prolong the progression-free survival (PFS) of patients with glioma within 18 months but can't prolong the OS. 47 Cetuximab and nimotuzumab target epidermal growth factor receptor (EGFR), which can block its ligand activity, induce apoptosis, antiangiogenesis, and thus achieve the effect of inhibiting GBM cells. 48 In a phase II clinical study of cetuximab treated in patients with relapsed GBM, cetuximab did not benefit patients from PFS and OS, regardless of whether accompanied by EGFR amplification.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Bevacizumab, which is an antiangiogenic agent by its ability to inhibit VEGF, has also been approved for use in glioblastoma patients (Avastin; FDA approval: 2009 for recurrent glioblastoma). However, trials have shown that treatment with Bevacizumab prolongs progression-free survival, but does not have any significant effect on overall survival [ 175 ].…”
Section: Clinical Targeting Of Glioblastoma: Is There An Anti-invasion/anti-migration Treatment?mentioning
confidence: 99%
“…BMI was calculated as weight (kg)/(height (m)) 2 , and the median values were 21.1 (15.5-29.2) for the bevacizumab group and 21.5 (15.9-33.8) for the non-bevacizumab group (P=0.64). No significant differences were found in chemotherapy cycles {6[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] vs. 6 [6-16]; P=0.68}, baseline spleen sizes [152.2 (74.1-529.6) vs. 150.0 (69.5-410.8); P=0.11] (cm 3 ), and baseline platelet counts {162 [77-441] vs. 166 [69-532]; P=0.90} (K/μL) between the two groups.…”
mentioning
confidence: 94%
“…Bevacizumab enhances the effect of chemotherapy in colorectal cancer and was approved by the FDA as the first angiogenesis inhibitor to treat metastatic colorectal cancer (mCRC) (5). However, it has several adverse effects including hypertension, proteinuria, thromboembolic events, wound-healing complications, congestive heart failure, and gastrointestinal perforation (6)(7)(8)(9)(10)(11). Bevacizumab plus oxaliplatin-based chemotherapy and bevacizumab plus irinotecan-based chemotherapy are equally effective.…”
Section: Introductionmentioning
confidence: 99%